Peran Guru PPKn Dalam Meminimalisir Kenakalan Remaja Pada Peserta Didik - Hikmah Mulia; Windi Hartati; Reza Mauldy Raharja (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The purpose of this research is to find out the steps used by PPKn teachers in dealing with juvenile delinquency among students at SMPN 27 Serang City, because what we already know is that juvenile delinquency in Indonesia often occurs, such as bullying, skipping school which has become a habit, smoking and even smoking. There are minors who are involved in brawls and even use illegal drugs or narcotics, in this case there is a need for teacher involvement in correcting juvenile delinquency among students, in overcoming this, especially civics teachers to help students overcome this by teaching them about morality, standars, and good behavior. This research uses a descriptive qualitative research design through observation, interviews, documentation and literature review to support the data obtained. The research finding the show that juvenile delinquency among students at SMPN 27 Serang City is a minor offense such as children not tucking in their clothes, playing truant or one of them teasing their friends and breaking the bathroom door. PPKn teachers are also responsible for being role models and facilitators, usually PPKn teachers. Every time you enter the classroom, teach students to accustom themselves to dress neatly, then instill an attitude of respect, tolerance, then look after the belongings of their classmates and the teacher also does not discriminate between smart and mediocre students, all are equal in accordance with the vision and mission at SMPN 27, Serang City, making the school a reality. Civilized, Creative, Active and Religious or abbreviated as BERKIBAR.